The Helsinki Affair - Pitoniak, Anna (New York : Simon & Schuster, 2023)
Amanda Cole is a brilliant young CIA agent, following in the footsteps of her father, Charlie. But Amanda's posting in Rome is a sleepy one. She's listless and looking for action when, on a hot summer day, it walks right through the door of her office. A lowly Russian operative is desperate, begging to speak to her. He tells her that a US Senator is about to be assassinated on an overseas trip to Cairo. Amanda believes he's telling the truth, but her superiors do not, and they determine that the best course of action is no action at all. But then the assassination occurs, and Amanda is suddenly thrust into an international conspiracy as she tries to find out why the Senator was killed. What did he know that made him a target of the KGB and the Kremlin? Amanda pairs up with the fast-talking Kath, a brash older woman and legendary spy, to get to the bottom of the case. The investigation takes them from Rome to London to Moscow to Helsinki. As Amanda and Kath get closer to solving the case, one question keeps coming back to haunt Amanda: why was her father's name written down in the Senator's notes that he seemed to be putting together right before he died? Was her father not the loyal CIA agent she always assumed he was? In order to get to the bottom of this international plot of blackmail, murder, and lies, Amanda must decide where her loyalty lies: with her country or with her family.
Keywords: Assassination -- Fiction; Conspiracies -- Fiction; Intelligence officers -- Fiction; Defectors -- Fiction; Fathers and daughters -- Fiction; Women intelligence officers -- Fiction